Comparative Analysis of Professional-Value Attitudes of the Youth in Russia and Kazakhstan in Education - Meruert K. Shnarbekova; Elena I. Vasileva; Tatiana E. Zerchaninova; Alena S. Nikitina (National Research Mordova State University, 2023)
Introduction. In the modern world, there is a global transition to a new value paradigm of education, upbringing, and professional self-determination. Therefore, the study of educational and professional attitudes of young people gains prominence. The aim of the research is to identify the factors influencing the formation of a system of value trajectories and attitudes of young people in Russia and Kazakhstan and to predict social scenarios for their development. Materials and Methods. To study the educational and professional value trajectories and attitudes of young people in Russia and Kazakhstan, the authors conducted an international empirical sociological study in 2021. The data collection method is a survey of young people aged 14-35 years living in Russia and Kazakhstan. Results. The analysis revealed a high level of socio-cultural, value potential of young people in Russia and Kazakhstan in the educational space. Young people from both countries point out the importance of higher education in personal and professional career growth and self-realization. The professional attitudes and desired professional orientations of the Russian and Kazakh youth are heterogeneous. The main factors in choosing a profession are the interest of the profession, it`s financially rewarding, and prestige of the educational institution. Risk factors include low demand for the profession in the labor market, lack of personal interest in the profession, and low income. As a possible scenario have been identified the demand for IT competencies in the Russian and Kazakhstan labor markets, the transformation of value-professional attitudes towards greater freedom and creativity, socio-professional mobility and flexibility of young people. Discussion and Conclusion. The obtained data and recommendations can be used by educational organizations, authorities implementing state policy in the field of education to improve the work on the formation and development of value trajectories and attitudes of young people in Russia and Kazakhstan in the educational space and in the field of professional self-determination.